(3YbO GddBdF GdeSJVjFI GdoeYOI dfaj GdJdHjS Yf GdoefJSHjf ddQShd NUhUoG efge EOQjS Hf EOQjSs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3hHYO aEfj deG bQCJ MOjK GdQShd ef GOYi CHkG ai GdGSe ZjQ CHjg aGdLfI Ydjg MQGe hcKjQ ef GdfGS jOYj GdTQa aWdH HYV GdCUMGH Cf CHjf ef PQjI GdQShd ef djS ajg EQJjGH s
(3BNQgG (B:s
(3aGddg jef Hg Ydi GdeDefjf , hHHQcGJg jScf QhYI GdeSdejf ced HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B241 - (3U(B274s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B342 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B288 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdQHGW (B(43 (3c(B) s
Keywords: (3GdJGQjNs